2013
DOI: 10.1111/clr.12199
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of single‐tooth implant‐supported zirconia‐based indirect composite‐layered molar restorations

Abstract: The fracture resistance of single-tooth implant-supported zirconia-based indirect composite-layered molar crowns primed with Estenia Opaque Primer for zirconia frameworks (ZIC-E) is comparable to that of porcelain-fused-to-metal (PFM) and zirconia-based all-ceramic (ZAC) restorations. Application of Estenia Opaque Primer to zirconia ceramic framework provides superior fracture resistance in implant-supported zirconia-based indirect composite-layered molar crowns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 31 publications
2
30
1
Order By: Relevance
“…Thus, all the present zirconia-based restorations have the potential to withstand physiologic masticatory forces. The fracture loads obtained in the current study might not differ from those of the previous study without fatigue testing (Table 2) 16) . This finding indicates that the zirconia-based porcelain-and composite-layered restorations presently tested can tolerate long-term masticatory stresses in the posterior region.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Thus, all the present zirconia-based restorations have the potential to withstand physiologic masticatory forces. The fracture loads obtained in the current study might not differ from those of the previous study without fatigue testing (Table 2) 16) . This finding indicates that the zirconia-based porcelain-and composite-layered restorations presently tested can tolerate long-term masticatory stresses in the posterior region.…”
Section: Discussioncontrasting
confidence: 48%
“…Adaptation of all completed specimens was verified with the same procedure used for the ZAC group. 16) . Different lowercase letters indicate a significant difference between means (Tukey's HSD test, p<0.05).…”
Section: Zic-p Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of bond strength of layering porcelain to zirconia frameworks [11][12][13][14] indicated that values were comparable to those of layering porcelain to metal alloy. Indirect composite materials -an alternative to feldspathic porcelain for layering materials-have recently been introduced for use with zirconia-based restorations [15][16][17][18] . Several studies found that the shear bond strength of indirect composite materials to zirconia frameworks was greater than 20 MPa 15,17) , which is above the threshold for clinically acceptable composite-metal and compositeceramic bonds 19,20) .…”
Section: Introductionmentioning
confidence: 99%
“…Fushiki et al 16) demonstrated that the use of a silane coupling agent and opaque material yielded stable bond strength of the indirect composite and feldspathicporcelain-coated zirconia, and suggested that feldspathic porcelain coating of zirconia frameworks was an effective method to achieve clinically acceptable bond strengths. Furthermore, an in vitro study indicated that the fracture resistance of implant-supported zirconia-based restorations, in which an indirect composite material was veneered onto zirconia frameworks pretreated with MDP-containing primer, was equal to that of porcelain-fused-to-metal or zirconia-based all-ceramic restorations 18) . Indirect composite materials have a beneficial effect on implant-supported posterior restorations.…”
Section: Introductionmentioning
confidence: 99%